Efektifitas Undang-Undang Perlindungan Anak Dalam Melindungi Anak Korban Tindak Pidana Perkosaan Oleh Orang Terdekat - Veren Martha Habel; Hadibah Zachra Wadjo; Judy Marria Saimima (TATOHI: Jurnal Ilmu Hukum, 2023)
Introduction: Protection for children takes the form of protection from acts of violence, whether physical violence, psychological violence, neglect, even sexual crimes.Purposes of the Research: The research objectives are; (1) to examine and explain the effectiveness of the Child Protection Law in protecting child victims of criminal acts of rape by those closest to them, (2) to examine and explain the obstacles experienced by investigators in handling criminal acts of child molestation.Methods of the Research: The author uses normative research methods, uses a factual approach and a statutory approach, normative legal research is also known as doctrinal legal research, and is then analyzed qualitatively descriptively to produce a conclusion.Results of the Research: Based on the research results obtained, consumer protection is all efforts made to protect interests and ensure legal certainty for consumers. In this effort, the rights and obligations of consumers and business actors cannot be separated. The Covid-19 pandemic has had a major impact on consumers' rights to comfort and safety in consuming goods and/or services in e-commerce agreements. Therefore, legal protection is needed for consumers, both preventively and repressively, so that every consumer's rights can be protected and their rights maintained.